(untitled) (Journal of Leadership, Accountability and Ethics, 2019)
This paper examines leadership. We present insights from a highly influential paper. Here are the highlights from this paper: This article intends to examine the role of leadership styles (transformational, transactional, and laissez-faire) and employees’ trust toward organizational change capacity (OCC). Data were collected from a convenient sample of managers, coordinators, officers, community facilitators, social organizers, and activists through questionnaires. A total of 250 respondents were sent questionnaires, usable questionnaires were 204. Results revealed positive and significant relationships between transformational leadership and employees’ trust. Moreover, an insignificant relationship was found between transactional leadership and employees’ trust, whereas laissez-faire and employees’ trust were found to be negatively associated. Findings of the study also depicted a positive and significant relationship of transformational leadership and transactional leadership with OCC. However, laissez-faire was negatively associated with OCC. Results also revealed that employees’ trust mediates the relationship between leadership styles (transformational and laissez-faire) and OCC. However, employees’ trust did not mediate the relationship between transactional leadership and OCC. Finally, implications and suggestions for future research are provided. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.